An Effective Approach to Teaching English to Science-Major Students in Science Universities: Hassan II University as a Case Study - HADDI, Loubna (Journal of Educational and Psychological Sciences, 2019)
This paper aims to shed light on the distinct challenges that Moroccan science-major postgraduates are facing, particularly at the end of their academic year, to publish their end-of-term projects in English. The article also uncovers certain weaknesses and misconceptions concerning the existing instructional methods. As an assistant professor with substantial experience teaching science-major students, a few alternative teaching practices will be discussed and recommended in the teaching of English in Moroccan universities, instead of the overused, traditional methods. In doing so, university students were interviewed and asked to rate some of what they thought were the best activities in English classes. As regards the research methodology, surveys and interviews were conducted first hand. The questionnaires were structured in advance with students who attend English classes. Through this instrument, data was collected on the students’ attitudes and their vision of the best practices in English classes, in particular when teaching English for Specific Purposes (ESP). The students showed a great preference for English for Specific Purposes over general English lessons due to the scientific nature of their studies, hence jobs. Also, because these lessons are taught at university level, the participants expressed favorable views about debates and open discussions. These and other findings aim at enriching the literature on education at tertiary levels and on the field of ESP.